Ethnographic Field Of Kamchatka: Characteristic Features And Research Problems - Igorevna Kirillova, Alina (Opción, 2019)
The article analyzes modern Kamchatka ethnographic studies. The author reveals peculiar features of Kamchatka’s ethnographic field and describes difficulties of local exploration. Modern historical exploration methods used in Russia and for- eign countries are described. The author uses monographs and papers by modern Russian and foreign scientists and her own field materials. The article is based on materials of two significant (in terms of population and prospects of ethno-tourism development) districts of Kamchatka, Bystrinskiy and Milkovskiy. Special atten- tion is paid to the practice of Russian field ethnological schools.